b y Lewis Carroll. - Carroll, Lewis, 1832-1898. ([United States] : Onyx Translations, 2015)
A little girl falls down a rabbit hole and discovers a world of nonsensical and amusing characters such as the Mad Hatter, the Queen of Hearts, and the Cheshire Cat.
Translation of: Alice's adventure in Wonderland.
Title supplied by OCLC WorldCat.
Text in Arabic.
Keywords: Fantasy; Arabic language materials